Evaluation of Silicon Supplementation for Drought Stress under Water-Deficit Conditions: An Application of Sustainable Agriculture - Muhammad Ahsan; Mohammad Valipour; Fahim Nawaz; Muhammad Raheel; Hafiz Tassawar Abbas; Mateen Sajid; Abdul Manan; Shamsa Kanwal; Eman A. Mahmoud; Ryan Casini; Hosam O. Elansary; Emanuele Radicetti; et al. (Agronomy, 2023)
Drought is a key abiotic stress that confines agriculture development worldwide. Silicon (Si) is commonly considered to be a valuable element for resistance against drought and for sustainable agriculture. To investigate the morpho-physiological and biochemical characteristics of Gerbera jamesonii plants, a pot experiment was conducted under greenhouse conditions and exposed to water stress (60% FC) and well-watered (100% FC) conditions. Foliar application of Si was carried out after ten days (48 days after sowing) of drought treatment and was repeated weekly, while well-water was regarded as control. Water deficiency significantly abridged the morphological attributes, pigments, and stress-related metabolites and negatively affected the photosynthetic apparatus in drought-stressed gerbera plants. However, Si supplementation by 40 mg L−1 produced increased leaf area (31%), stem length (25%), flower diameter (22%), plant fresh biomass (17%), total chlorophyll (48%), and concentration of carotenoids (54%) in water-stressed plants. Similarly, the accretion of a total free amino acid (41%) and the activities of peroxidase, catalase, superoxide dismutase, ascorbate peroxidase, glycinebetaine, total soluble proteins, total free proline, and malondialdehyde were enhanced by 44%, 31%, 53%, 33%, 330%, 61%, 51%, and 66%, respectively, under drought stress in comparison with control conditions. Meanwhile, the photosynthetic rate (89%), the transpiration rate (12%), and stomatal conductance (55%) were significantly enhanced in water-deficit gerbera leaves with Si supplementation. This study proposes that the foliar application of Si is a viable and convenient method of improving the performance of elegant gerbera flower plants in regions of the world that are facing severe water deficiency.